Fiqh Anak di Indonesia - Rizal Darwis (Al-Ulum, 2010)
This article describes the concept of children fiqh in Indonesia with discussions covering status and child care. A child can legitimately be said to have a blood relationship with her/his father if she/he was born in a legitimate marriage. If the child is born illegitimately; then, she/he cannot be attributed to his/her father, except his/her mother alone. In the case of child care, most scholars have differed fiqh perspective. Many fiqh scholars stated that women has the authority to care for and educate children is more appropriate care for and educate children because their feminine nature. However, Hanafi and Maliki schools of thought argued that nurturing, caring and educating children is the right caregiver (mother or a representative). Associated Muslim scholars contended that the right of al-hadhanah is the rights of the two parents. Wahbah al-Zuhailiy argued that the rights of alhadhanah belong to association between mother, father and children. If a dispute arises among these three parties; then, the priority is focused on the rights of the cared-child.